1993
DOI: 10.1093/ptj/73.12.857
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of Muscles and Their Motor Nuclei: The Partitioning Hypothesis

Abstract: This review article is designed to expose physical therapists to an examination of muscle organization and the implications that this organization has for therapeutic applications. The partitioning hypothesis is based on the fact that an individual muscle is arranged in a more complex array than simply fibers attaching at aponeuroses, tendons, or bones with a single muscle nerve innervation. Neuromuscular compartments, which are distinct subvolumes of a muscle, each innervated by an individual muscle nerve bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
127
1
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 42 publications
13
127
1
4
Order By: Relevance
“…In addition, the motor point is the skin surface at which the maximal mechanical response is elicited with the minimum applied current. However, English et al 14 described a more complex organization of the studied region. They indicated that the nerve or primary motor branch continues its path inside the muscle, dividing into two or more secondary branches that reach the NMCs 14,31 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the motor point is the skin surface at which the maximal mechanical response is elicited with the minimum applied current. However, English et al 14 described a more complex organization of the studied region. They indicated that the nerve or primary motor branch continues its path inside the muscle, dividing into two or more secondary branches that reach the NMCs 14,31 .…”
Section: Discussionmentioning
confidence: 95%
“…The knowledge of the actions of muscle groups and of each muscle that constitutes them, as well as the contribution of each NMC to the final action of the muscle, is fundamental for the effective rehabilitation of patients afflicted by neurological and muscle dysfunctions that impede basic movements, such as walking, jumping, sitting, and standing, as well as more demanding activities, such as sports 14,15 . These movements require the constant activation of stabilizing muscles in static and dynamic positions at the joints of the lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, muscles in various mammalian species have been shown to consist of multiple functional subdivisions (Burke, 1995;English et al, 1993;Windhorst et al, 1989). Within such a muscle, each subdivision consists of a region of muscle fibers innervated by a separate branch of the muscle nerve (English and Letbetter, 1982;English and Weeks, 1984;Balice-Gordon and Thompson, 1988;English, 1990;Segal et al, 1991;Drake et al, 1993;Serlin and Schieber, 1993;Sanders, et al, 1994;Vanden Noven et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…De acuerdo con English et al (1993), cada compartimiento contiene unidades motoras con un único ordenamiento de atributos fisiológicos. Por su acción sobre la articulación de la rodilla el músculo bíceps femoral constituye uno de los principales actores en la estabilidad estática y dinámica del miembro pelviano del canino.…”
Section: Introductionunclassified
“…Los músculos esqueléticos de los mamíferos están compuestos por subvolúmenes denominados compartimientos neuromusculares, en los cuales pueden variar el diseño arquitectónico macroscópico y las características de las fibras. Kernell (1998), define al compartimiento neuromuscular como subvolúmenes inervados exclusivamente por una rama primaria del nervio, con una población fibrilar y arquitectura características.De acuerdo con English et al (1993), cada compartimiento contiene unidades motoras con un único ordenamiento de atributos fisiológicos. Por su acción sobre la articulación de la rodilla el músculo bíceps femoral constituye uno de los principales actores en la estabilidad estática y dinámica del miembro pelviano del canino.…”
unclassified